Renaissance and Reformation, 1500-1620 : a biographical dictionary - Carney, Jo Eldridge, 1954- (Great cultural eras of the Western world., 2001)
Provides basic information on the people who have contributed significantly to the culture of Western civilization. Covers such figures as the religious leaders who contributed to the Reformation, scientists who paved the way for a new view of the universe, and Renaissance painters, sculptors, and architects, as well as writers, musicians, and scholars.